Từ \(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\Rightarrow\frac{a^2+b^2}{c^2+d^2}=\frac{2ab}{2cd}\)
Áp dụng tính chất của dãy tỉ số bằng nhau a có:
\(\frac{a^2+b^2}{c^2+d^2}=\frac{2ab}{2cd}=\frac{a^2+b^2-2ab}{c^2+d^2-2cd}=\frac{a^2+b^2+2ab}{c^2+d^2+2cd}\Rightarrow\frac{\left(a-b\right)^2}{\left(c-d\right)^2}=\frac{\left(a+b\right)^2}{\left(c+d\right)^2}\)
\(\Rightarrow\frac{a-b}{c-d}=\frac{a+b}{c+d}=\frac{a-b+a+b}{c-d+c+d}=\frac{2a}{2c}=\frac{a}{c}=\frac{a-b-a-b}{c-d-c-d}=-\frac{2b}{-2d}=\frac{b}{d}\)
=>\(\frac{a}{b}=\frac{c}{d}\)
ta có \(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\left(a,b,c,d\ne0;c\ne\pm d\right)\)
\(\Rightarrow\)cd(a2+b2)=ab(c2+d2)\(\Rightarrow\)a2cd+b2cd=abc2+abd2
\(\Rightarrow\)a2cd-abc2=abd2-b2cd \(\Rightarrow\)ac(ad-bc)=bd(ad-bc)
\(\Rightarrow\)(ad-bc) (ac-bd)=0\(\Rightarrow\orbr{\begin{cases}ad-bc=0\\ac-bd=0\end{cases}}\Rightarrow\orbr{\begin{cases}ad=bc\\ac=bd\end{cases}}\Rightarrow\orbr{\begin{cases}\frac{a}{b}=\frac{c}{d}\\\frac{a}{b}=\frac{d}{c}\end{cases}}\)(DPCM)